A cross-sectional study of the current status of psychological health and its correlation with academic performance in medical students: taking medical students in a medical university in China as examples - Han Chunhong; Han Chunhong; Ding Jingjing; He Huan; Zheng Peiyao; Zhang Xiaona; Yang Xiaowen; Zheng Aiming (Frontiers in Psychiatry)
BackgroundThe psychological health problems are becoming increasingly prominent among medical students under the heavy academic stress and high-intensity clinical internships. This study examines the psychological health of medical students in a Chinese university and its impact on academic performance, aiming to inform targeted interventions.Methods2022 undergraduate and postgraduates from an independent medical university in Eastern China were selected to score using the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7(GAD-7), Insomnia Severity Index (ISI), Perceived Stress Scale (PSS), and Beck Scale for Suicide Ideation(BSSI); and the total grade point averages (GPAs) of 2022 undergraduates in the first and second academic years were determined to analyse the main psychological influencing factors.ResultsThe general survey of 2022 new medical students at admission showed that the various scores of postgraduates were higher than those of undergraduates. After two semesters, the percentage of students scored higher in unhealthy psychology indicators was increased in both postgraduates and undergraduates, but the differences between two groups were decreased. Analysis of the first and second-year academic performances of 2022 undergraduates revealed that assessment scores of PHQ-9, PSS, ISI, and BSSI had a correlation with the total GPA. However, no correlation was found between the GAD-7 values and the GPA. The PHQ-9 scores and major categories were identified as independent factors influencing the average GPA.ConclusionThe undergraduates face significant challenges in depression, anxiety, insomnia, and perceived stress, and these have negative effects on their academic performances; in particular, the depressive symptoms and perceived stress can significantly reduce their academic performances. In contrast, the psychological health statuses in the postgraduates tend to deteriorate as the semester progress.